The Impact of Transformational Leadership on the Job Performance of Employees in Contemporary Healthcare Institutions "A Field Study on the Management of Five Health Services" (Comprehensive Journal of Science, 2025)
This study aimed to identify the impact of transformational leadership on the level of job performance in contemporary institutions, through a field study conducted on the health services departments in the city of Al-Khums. To achieve the objectives of the study, the descriptive-analytical method was adopted, and a questionnaire was used as the data collection tool. The questionnaire was distributed to 140 employees working in the health services departments of Al-Khums, with a response rate of 93%. Data were analyzed using computer software and the SPSS statistical package, relying on percentages, arithmetic means, and standard deviations, in addition to multiple regression analysis and one-way ANOVA.The study reached several findings, most notably the existence of a statistically significant effect of the dimension of idealized influence on the level of job performance in the health services departments of Al-Khums. However, no statistically significant effect was found for the dimensions of inspirational motivation, intellectual stimulation, and individualized consideration on job and organizational performance in these departments, from the employees’ perspective. In light of these results, the study presented a set of practical recommendations.
Keywords: Transformational Leadership, Job Performance, Contemporary Health Institutions, Health Services Management in the City of Al Khums